The Effect of Collaborative Paragraph Writing Technique Toward Students’ Writing Skill on Recount Paragraph At Grade X of SMAN 1 Batang Anai - Syamsuarni Syamsuarni; Jufrizal Jufrizal; Yenni Rozimela (International Journal of Educational Dynamics, 2020)
This article observes the effect of collaborative paragraph writing technique toward students’ writing skill on recount paragraph. The research was an experimental research. The instruments of the research were writing test. It was conducted for 4 weeks (8 meetings) to the grade X students of SMAN 1 Batang Anai. Class X1 which consisted of 33 students was an experimental group, whereas class X2 which also consisted of 33 students was a control group. The instrument of the research was writing test. The writing test was given as a post test to both classes at the end of the research. The data of the research were analyzed by using t-test. The result shows that collaborative paragraph writing technique gave significant effect toward students’ writing skill on recount paragraph as it was compared to conventional technique that was usually used by the teacher in teaching writing. Based on the result, it is suggested to English teachers at SMA level to apply this collaborative paragraph writing technique as an alternative technique in teaching writing in English.